IRONIE ET ARGUMENTATION DANS LE DISCOURS PARLEMENTAIRE PORTUGAIS - PEREIRA BRAZ, Ana Cristina (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Irony and argumentation in Portuguese parliamentary discourse. The aim of this paper is to study argumentation in political discourse, namely in parliamentary discourse, the focus being the relations between irony and argumentation. Since Antiquity, irony has been seen as a rhetorical device, used in oratory for purposes of discourse efficiency. The present day political discourse stems from the same rhetorical tradition. Being one of the favourite discursive mechanisms of political persuasion, irony is an argumentative device common in parliamentary debates, a highly controversial and confrontational discursive subgenre, where opposite parties clash. By its evaluative nature and perlocutionary effect of criticizing the political opponents, irony contributes to the argumentation process, relying particularly on the images that it creates. The corpus we analyse contains excerpts of speeches given in plenary sittings that took place in the Portuguese Assembly between September 15th, 2010 and May 19th, 2011. Rezumat. Ironie și argumentare în discursul parlamentar portughez. Această lucrare își propune să studieze argumentarea în discursul politic, și anume în discursul parlamentar, concentrându-se îndeosebi asupra relațiilor dintre ironie și argumentare. Încă din antichitate, ironia a fost percepută ca strategie retorică și a fost folosită de oratori pentru a-și atinge obiectivele discursive. Discursul politic din zilele noastre se revendică din aceeași tradiție retorică. Unul dintre mecanismele discursive predilecte în persuasiunea politică, ironia este o strategie argumentativă comună în dezbaterile parlamentare, un gen discursiv plin de confruntări, în care forțe antagonice se opun una alteia. Prin natura sa evaluativă și prin efectul perlocuționar de critică a oponenților politici, ironia contribuie la procesul argumentativ, în special prin imaginile pe care le creează. Corpusul pe care îl analizăm conține fragmente din intervenții în sesiune plenare care au avut loc în Parlamentul Portughez în perioada 15 septembrie 2010 – 19 mai 2011. Cuvinte cheie: ironie, argumentare, retorică, persuasiune, discurs parlamentar, imagine, ethos, pathos